E-cigarettes: an acceptable alternative to smoking for breastfeeding mothers? - Johnston, Emily (2020)
Despite many women quitting smoking during pregnancy, the majority will return to smoking by 12 months postpartum. Smoking postpartum carries substantial risks of morbidity and mortality for both mother and baby. Breastfeeding is a protective factor against some of the risks associated with smoking. However, mothers who smoke are less likely to intend to breastfeed, initiate breastfeeding at birth, or continue breastfeeding, than non-smoking mothers. Current explanations for this association include a possible physiological mechanism, a coincidental association due to shared demographics, or a fear of harm.